Asia-Gulf economic relations in the 21st century : the local to global transformation - Malik, Monica; Niblock, Tim (Gerlach Press, 2013)
Asia constitutes the hub of the transformation of global economic power today. The Gulf, itself part of Asia, is of increasing importance in this transformation. This book documents the growing interactions between the economies of the Gulf states and those of the rest of Asia. These relationships are critical to how the world economy develops over the next decade, and how economic (and perhaps strategic) power is distributed. This volume assembles cutting-edge thinking by 16 specialists on a wide variety of topics covering Arab Gulf relations with China, Japan, ASEAN, Korea and India.